2016
DOI: 10.18632/oncotarget.7361
|View full text |Cite
|
Sign up to set email alerts
|

Cross-platform comparison of independent datasets identifies an immune signature associated with improved survival in metastatic melanoma

Abstract: Platform and study differences in prognostic signatures from metastatic melanoma (MM) gene expression reports often hinder consensus arrival. We performed survival/outcome-based pairwise comparisons of three independent MM gene expression profiles using the threshold-free algorithm rank-rank hypergeometric overlap analysis (RRHO). We found statistically significant overlap for genes overexpressed in favorable outcome (FO) groups, but no overlap for poor outcome (PO) groups. This “favorable outcome signature” (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
(55 reference statements)
2
13
0
Order By: Relevance
“…Genomic signatures seem to play a key role in patient outcomes in BRAF V600 -mutated melanoma. Increased tumor immune gene expression (both activating and suppressive genes) and low cellcycle gene expression are associated with longer PFS in vemurafenib-treated patients, consistent with what has been shown previously with other treatments in melanoma (9)(10)(11)(12)16). In contrast, increased expression of cell-cycle genes and low immune-related gene expression was associated with shorter PFS in patients treated with vemurafenib monotherapy, while comparable PFS outcomes for cell-cycle and immune signatures were seen in patients treated with cobimetinib and vemurafenib.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Genomic signatures seem to play a key role in patient outcomes in BRAF V600 -mutated melanoma. Increased tumor immune gene expression (both activating and suppressive genes) and low cellcycle gene expression are associated with longer PFS in vemurafenib-treated patients, consistent with what has been shown previously with other treatments in melanoma (9)(10)(11)(12)16). In contrast, increased expression of cell-cycle genes and low immune-related gene expression was associated with shorter PFS in patients treated with vemurafenib monotherapy, while comparable PFS outcomes for cell-cycle and immune signatures were seen in patients treated with cobimetinib and vemurafenib.…”
Section: Discussionsupporting
confidence: 85%
“…The observation of better PFS associated with the immune signature is consistent with previous observations. Pretreatment immune context has previously been shown to be associated with outcomes in patients with metastatic melanoma (9)(10)(11)(12)16) as well as in other cancer types (17). However, these signatures were not developed in the context of molecularly targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a strong immunological host response is considered to be prognostically favorable. Lardone et al compared three independent gene expression studies and found a common immune gene signature of T cell-associated genes among favorable outcome patients with stage III-IV CMM [ 16 ]. Several studies have demonstrated that presence of tumor infiltrating lymphocytes (TILs) in primary tumors is associated with a better clinical outcome [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytes, for example, T helper cells (T H cells) can foster cytotoxic T cell antitumor activity and vividly interact with antigen presenting cells in or near the tumor microenvironment to mount cellular and humoral immune responses, often also forming local tertiary lymphoid structures (TLS) . Lymphocytes can be categorized into naïve cells, that have not encountered their antigen yet, and effector/memory cells.…”
Section: Introductionmentioning
confidence: 99%